1991
DOI: 10.1093/jac/28.suppl_c.31
|View full text |Cite
|
Sign up to set email alerts
|

A review of antibiotic resistance patterns of Streptococcus pneumoniae in Europe

Abstract: Streptococcus pneumoniae no longer has predictable antibiotic susceptibility. There are two areas of high prevalence of resistance (over 25%) to beta-lactam antibiotics in the South-West and North-East of Europe. In Spain, a close relationship has been found between the yearly rate of aminopenicillin consumption and penicillin resistance. High level resistance (MIC greater than or equal to 1 mg/L) has developed against a previous background of low level resistance. The serotypes involved in penicillin resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
90
0
3

Year Published

1996
1996
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(96 citation statements)
references
References 11 publications
3
90
0
3
Order By: Relevance
“…Several studies have shown that the occurrence of resistance is closely related to the medical use of a drug, even though the association may be variable (11,15,26). This association has also been demonstrated for antimicrobial agents used for growth promotion (4,6,9).…”
mentioning
confidence: 93%
“…Several studies have shown that the occurrence of resistance is closely related to the medical use of a drug, even though the association may be variable (11,15,26). This association has also been demonstrated for antimicrobial agents used for growth promotion (4,6,9).…”
mentioning
confidence: 93%
“…Moreover, the PRP has been reported to harbour resistance to other antimicrobial classes, thus making the treatment much more difficult [12]. Multidrug resistance (MDR) of pneumococci was first reported in 1977 in South Africa and subsequently in Europe [13] and United states [14]. Since then, low levels of MDR have been reported from few regions of India.…”
Section: Introductionmentioning
confidence: 99%
“…According to data collected by the National Pneumococcus Reference Center in France (63) in 2002, strains with decreased susceptibility to penicillin (MIC Ͼ 0.1 g/ml) accounted for 53% of invasive pneumococcal infections, whereas only 8% of strains from adults with bacteremic pneumonia were resistant to penicillin (MIC Ͼ 1 g/ml). Penicillin-resistant strains exhibit variable patterns of resistance to other beta-lactams and are usually resistant to other classes of antibiotics that are active against pneumococci (12,34,53,54,55). The overall mortality rate in patients with S. pneumoniae pneumonia is about 10% (25).…”
mentioning
confidence: 99%